2019
DOI: 10.2135/cropsci2018.11.0700
|View full text |Cite
|
Sign up to set email alerts
|

Response of Grain Quality to Alternate Wetting and Moderate Soil Drying Irrigation in Rice

Abstract: Alternate wetting and moderate soil drying irrigation (WMD) has been widely adopted in rice (Oryza sativa L.) production for saving irrigation water and increasing grain yield. However, limited information is available about the effect of WMD on rice grain quality. The main purpose of this study was to evaluate the characteristics of grain quality in response to WMD. Two rice varieties, Yangdao 6 (YD6, indica) and Hanyou 8 (HY8, japonica), were grown in the field, with two water management treatments, well‐wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 53 publications
4
23
3
Order By: Relevance
“…For a few elements, our results are different from those recently reported by Xu and coworkers [18], who compared CF with a moderate soil dry irrigation. In particular, for Mn and Zn their results are essentially consistent with ours, whereas these authors reported that Cu and Fe concentrations decreased in the water-saving regime and in our conditions the Cu concentrations increased and Fe did not show any change (Table 6).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For a few elements, our results are different from those recently reported by Xu and coworkers [18], who compared CF with a moderate soil dry irrigation. In particular, for Mn and Zn their results are essentially consistent with ours, whereas these authors reported that Cu and Fe concentrations decreased in the water-saving regime and in our conditions the Cu concentrations increased and Fe did not show any change (Table 6).…”
Section: Discussioncontrasting
confidence: 99%
“…Different effects of AWD on the concentrations of Cd and As are reported in the literature. The behavior observed in our conditions (increased Cd accumulation and decreased As accumulation in AWD in both years) is in agreement with the results reported by Norton et al [49], but is different, for what concerns Cd, from the results by Xu et al [18], who did not observe any effect of AWD, and, for what concerns As, from the results of Carrijo et al [50], who observed effects on As accumulation only in severe AWD. Most probably these differences depend on the different timing and severity of the imposed AWD condition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of grain quality, controlled irrigation improved head rice percentage, chalkiness, and protein content (Xu et al, 2019), although little information is available on the effect of controlled soil drying on grain nutrition and safety. With improvements in living standards, rice breeding has shifted from focusing simply on production to yield and quality simultaneously (Gu et al, 2015).…”
Section: Crop Sciencementioning
confidence: 99%
“…In addition to varieties, environments effect by water regimes on the variation of nutritional accumulation in rice have been reported from previous references. The nutrients Cu, Fe, Mn, Mo, Se and Zn in bran and milled rice of non-pigmented rice were decreased by the moderate soil drying when compared with well watered (Xu et al, 2019). Wang et al (2014) reported that alternate wetting and drying (AWD) significantly increased Zn concentration and grain yield.…”
Section: Introductionmentioning
confidence: 99%